A facile approach for the preparation of reversible color changing luminescent fiber using thermochromic dyes. (December 2021) - Shi, Muyang; Lu, Bohui; Jin, Yang; Ge, Mingqiao
Abstract: The development of thermosensitive luminescent fiber (TLF) is of great significance for flexible wearable devices. Herein, reversible color changing luminescent fibers were successfully fabricated via wet-spinning of mixing Sr2 ZnSi2 O7 : Eu 2+, Dy 3+ (SZSO), Y2 O2 S: Eu 3+, Mg 2+, Ti 4+ (YOS) and blue thermochromic dye (BTD). The UV–vis absorption and photoluminescence emission spectra revealed the existence of an interaction impact between components. The TLF exhibited desirable thermochromic luminescent performance with a color transition temperature of 40 °C. The color of the TLF changed from dark blue (20 °C) turned to colorless (40 °C) under illuminant D65 (artificial daylight 6500 K), reversibly. After the stoppage of UV excitation and in darkness, TLF emitted blue luminescence while cooling and turned magenta as the temperature rose, which is originated from the conjugation structure conversion of BTD. The luminescence color depended on the temperature. And the TLF possessed a good thermostability up to 200 °C. This work indicates a simple and inexpensive method for anticounterfeiting and safety early-warning, and provides some new insights to prepare flexible sensor. Highlights: A novel thermosensitive luminescent fiber (TLF) was prepared in a facile way. The TLF can change the luminescent color according to the ambient temperature. The TLF exhibited desirable thermochromic luminescent performance.